Biodiesel production from microbial oil derived from wood isolate Trichoderma reesei. (September 2017) - Bharathiraja, B.; Sowmya, V.; Sridharan, Sridevi; Yuvaraj, D.; Jayamuthunagai, J.; Praveenkumar, R.
Graphical abstract: Highlights: T. reesei biodiesel properties meet international specifications. The yields of various extraction strategies were compared. Ultrasonication conditions were optimized for maximum lipid yield. Transesterification efficiency of various catalysts are illustrated. Abstract: In the present study Trichoderma reesei, a wood isolate can yield high biomass quantities up to 30 g/L, yielding 32.4% of lipids of dry cell weight (DCW). Biodiesel production from Trichoderma reesei involved simple unit operations like filtration and ultrasonication, yet giving good lipid yield with desirable bio-diesel properties. Optimization of ultrasonication conditions was done to ensure maximum lipid extraction. SEM analysis of ultrasonicated samples showed distinct breakage of fungal hyphae. The lipids were found to contain 49.7% saturated fatty acids. Transesterification using chemical and biological catalysts were compared and 96.09% efficiency was observed for lipase-catalyzed transesterification. The bio-diesel properties satisfied ASTM and EN specifications with cetane number: 53.1, iodine value: 63.34 g, saponification value: 235.07 mg KOH/g, cold flow plugging point: 9.13 °C.